2017
DOI: 10.3141/2633-03
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Hamburg Wheel-Tracking Test to Characterize Asphalt Mixtures in Cool Weather Regions

Abstract: The Hamburg wheel-tracking test (HWTT) has shown promise to predict permanent deformation resistance and moisture damage potential of asphalt mixtures. Several state agencies have implemented the test as a mixture evaluation and design tool. One aspect of the test that remains a topic of research is the testing temperature. Many studies and specifications use 50°C for all testing, but some use a test temperature that depends on the base asphalt used in the mixture. Concern exists about the use of 50°C as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In colder climates such as Wisconsin, lower temperatures have been used to evaluate the rutting resistance of the mixtures. Swiertz et al [10] performed the Hamburg test at 45 and 50 ℃ and observed that the number of passes to reach 12.5 mm of rut depth at 50 ℃ could be as high as three times higher than that at 45 ℃. Considering four nominal maximum aggregate sizes (NMAS) including 25, 19, 12.5, 9.5, and 4.75 mm of Superpave mixtures, Swiertz et al [10] investigated the effect of aggregate gradation on the rut depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In colder climates such as Wisconsin, lower temperatures have been used to evaluate the rutting resistance of the mixtures. Swiertz et al [10] performed the Hamburg test at 45 and 50 ℃ and observed that the number of passes to reach 12.5 mm of rut depth at 50 ℃ could be as high as three times higher than that at 45 ℃. Considering four nominal maximum aggregate sizes (NMAS) including 25, 19, 12.5, 9.5, and 4.75 mm of Superpave mixtures, Swiertz et al [10] investigated the effect of aggregate gradation on the rut depth.…”
Section: Introductionmentioning
confidence: 99%
“…Swiertz et al [10] performed the Hamburg test at 45 and 50 ℃ and observed that the number of passes to reach 12.5 mm of rut depth at 50 ℃ could be as high as three times higher than that at 45 ℃. Considering four nominal maximum aggregate sizes (NMAS) including 25, 19, 12.5, 9.5, and 4.75 mm of Superpave mixtures, Swiertz et al [10] investigated the effect of aggregate gradation on the rut depth. The Hamburg testing results at 50 ℃ under 20,000 wheel passes showed that the rut depth slightly increased as the NMAS increased from 4.75 to 25 mm.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, Walubita et al ( 28 ) performed the Hamburg test at 50°C, 60°C, and 70°C. Swiertz et al ( 29 ) also investigated the appropriate testing temperature for the Hamburg wheel tracking test when used in a colder climate. In that study, conducted in Wisconsin, tests were carried out at 40°C, 45°C, and 50°C.…”
mentioning
confidence: 99%